Amphetamine-Type-Stimulants (ATS) Use and Homosexuality-Related Enacted Stigma Are Associated With Depression Among Men Who Have Sex With Men (MSM) in Two Major Cities in Vietnam in 2014. (19th September 2017) - Vu, Nga Thi Thu; Holt, Martin; Phan, Huong Thi Thu; La, Lan Thi; Tran, Gioi Minh; Doan, Tung Thanh; Nguyen, Trang Nguyen Nhu; de Wit, John
ABSTRACT: Background : Men who have sex with men (MSM) are disproportionately affected by mental health concerns, including depression. Amphetamine-type-stimulants (ATS) use and homosexuality-related stigma and discrimination have been found associated with depression among MSM. Objectives : To assess the prevalence of depression and its associations with ATS use and homosexuality-related stigma and discrimination among MSM in Vietnam. Methods : 622 MSM were conveniently recruited in Hanoi and Ho Chi Minh city, Vietnam, from September to December 2014. We collected information on demographic characteristics, ATS, alcohol and other drug use, sexual behaviors, homosexuality-related and discrimination stigma, and sexual sensation-seeking. Depression and suicidal thoughts were assessed by the Patient Health Questionnaire (PHQ-9). We assessed associations of depression with ATS use and homosexuality-related stigma and discrimination using logistic regression. Results : Of 622 sampled MSM, 11.3% were classified as having major depression, 9.8% reported any suicidal thoughts in the last two weeks, 30.4% ever had used any ATS, 88.8% ever ad drank alcohol and 21.5% had ever used any other drugs. In multivariate analysis, depression was significantly associated with ATS use (Adjusted Odds Ratio [AOR: 2.20; (95% Confidence Interval (CI): 1.32–3.67], younger age of sexual debut with another man (AOR: 0.09; 95% CI: 0.02–0.50), and greater enacted homosexuality-related stigma (AOR: 1.97; 95% CI: 1.19–3.26). Conclusions : We found a moderate prevalence of depression among sampled MSM, which was associated with ATS use and enacted homosexuality-related stigma. We recommend integrating assessment and interventions regarding depression and methamphetamine use into gay-friendly, culturally adapted holistic HIV prevention for MSM in Vietnam.